Pectin-conjugated silica microcapsules as dual-responsive carriers for increasing the stability and antimicrobial efficacy of kasugamycin. (15th September 2017) - Fan, Chen; Guo, Mingcheng; Liang, You; Dong, Hongqiang; Ding, Guanglong; Zhang, Wenbing; Tang, Gang; Yang, Jiale; Kong, Dandan; Cao, Yongsong
Graphical abstract: Highlights: The microcapsules were prepared using pectin conjugated hollow silica spheres. The obtained microcapsules had a high loading ability for kasugamycin. The microcapsules displayed excellent pectinase and GSH dual-responsive properties. The prepared microcapsules had good photo- and thermal stability. The kasugamycin microcapsules showed sustained antimicrobial efficacy. Abstract: Kasugamycin is an aminoglycoside antibiotic originally isolated from Streptomyces kasugaensis, which has been widely used for the management of plant diseases. However, photo-thermal instability and low efficiency limit its application. Therefore, it is an urgent task to prevent unwanted loss of kasugamycin and ensure maximum bioactivity at target site. In this work, a novel formulation of kasugamycin that responds to different biological stimuli produced by pests was prepared using silica microcapsules crosslinked with pectin via special disulfide bonds. The results demonstrated that the silica-SS-pectin microcapsules had a high loading efficiency (20% w/w) and could effectively enhance the thermal and light stability of kasugamycin. The microcapsules displayed excellent pectinase and glutathione dual-responsive properties and the release kinetics investigated by Riger-Peppas model suggested combination of various release mechanisms. Compared with kasugamycin wettable powder, the microcapsules possessed sustained and improved antimicrobial efficacy against Erwinia carotovora . Thus, the dual-responsive microcapsules potentially have agricultural application as a controlled release system.